2012
DOI: 10.1051/0004-6361/201118617
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic weak-lensing shear spectra from largeN-body and hydrodynamical simulations

Abstract: Context. Forthcoming experiments will enable us to determine tomographic shear spectra at a high precision level. Most predictions about them have until now been based on algorithms yielding the expected linear and non-linear spectrum of density fluctuations. Even when simulations have been used, so-called Halofit predictions on fairly large scales have been needed. Aims. We wish to go beyond this limitation. Methods. We perform N-body and hydrodynamical simulations within a sufficiently large cosmological vol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Pedrosa, Tissera & Scannapieco 2009; Duffy et al 2010; Tissera et al 2010). In line with this result on halo concentration, also the total matter power spectrum in radiative hydrodynamic simulations has been shown to have a higher amplitude than for DM‐only N ‐body simulations, small non‐linear scales k > 1 h Mpc −1 (Jing et al 2006; Rudd et al 2008; van Daalen et al 2011; Casarini et al 2012). However, also the simple case of non‐radiative hydrodynamics has been suggested to increase halo concentration, as a consequence of a redistribution of energy between baryons and DM during halo collapse (Rasia, Tormen & Moscardini 2004; Lin et al 2006).…”
Section: Introductionsupporting
confidence: 65%
“…Pedrosa, Tissera & Scannapieco 2009; Duffy et al 2010; Tissera et al 2010). In line with this result on halo concentration, also the total matter power spectrum in radiative hydrodynamic simulations has been shown to have a higher amplitude than for DM‐only N ‐body simulations, small non‐linear scales k > 1 h Mpc −1 (Jing et al 2006; Rudd et al 2008; van Daalen et al 2011; Casarini et al 2012). However, also the simple case of non‐radiative hydrodynamics has been suggested to increase halo concentration, as a consequence of a redistribution of energy between baryons and DM during halo collapse (Rasia, Tormen & Moscardini 2004; Lin et al 2006).…”
Section: Introductionsupporting
confidence: 65%
“…Jing et al (2006), Rudd et al (2008), Guillet et al (2010), Casarini et al (2012) all confirmed the significance of baryonic feedback at k > 1h Mpc −1 by comparing hydrodynamical simulations to pure N-body dark matter ones. Schaye et al (2010) .…”
Section: Baryonic Feedbackmentioning
confidence: 59%
“…Notice that in real-space, these estimators are very efficient at excluding small-scale modes in the shear correlation functions. Thus these estimators can be used to help render cosmic shear measurements insensitive to potential systematic effects on small scales, like baryonic effects in the matter power spectrum (e.g., Zhan & Knox 2004;White 2004;Rudd et al 2008;van Daalen et al 2011;Casarini et al 2012) or the small-scale selection effects in shear measurements (e.g., Hartlap et al 2011). Similarly, these estimators do not use the shear correlation functions at zero separation, rendering them unbiased by shape noise.…”
Section: The Estimatorsmentioning
confidence: 99%